Preoperative Picture Improves Postoperative Satisfaction in Bunion Surgery. Issue 3 (14th September 2018) - Taylor, Michel
Category: Bunion Introduction/Purpose: Hallux valgus (HV) is the most common conditions affecting the forefoot. Typically, the patient's main concern is a prominent medial eminence (bunion) with difficulty with shoe wear and the cosmetic appearance of the toe. Patient satisfaction following HV correction surgery is between 73-94% however a poor cosmetic result can have a negative impact on the post-operative outcome. There is surprisingly a dearth of knowledge in the forefoot literature exploring the impact of cosmesis on the subjective outcome following HV surgery. The purpose of this prospective, blinded, randomized trial is to determine whether showing patients a preoperative photograph would improve post-operative satisfaction following HV corrective surgery. Methods: Patients undergoing HV corrective surgery were randomized to a picture group (P) or no picture group (NP). Inclusion criteria were patients over 18 and a diagnosis of HV. Pre-operatively, all patients had a picture taken of the operative foot. Patients were seen in follow up at 3 and 6 weeks and 3 months. P-group patients were shown the picture by the research assistant for 5 minutes at each visit. Patients completed the FFI and FAOS pre-operatively and at each post-operative visit. Patients also completed a satisfaction questionnaire at each post-operative visit which included a 5-point scale addressing overall satisfaction, satisfaction with the appearance of the foot and whether they would undergo the procedure again. Pre-operative and post-operative HVA and IMA were recorded by a fellowship trained orthopaedic surgeon not involved in the patient's care. The operative surgeon was blinded to the treatment groups. Results: 29 patients were enrolled in the study (15P). No difference with respect to age, gender, smoking, presence of comorbidities, underlying diagnosis, HVA or IMA, FFI or FAOS. At 3 months, patients in the picture group were more likely to be "completely satisfied" with the appearance of their foot and this difference was statistically significant (p<0.05). There were no differences between treatment groups with respect to post-operative HVA, IMA, FAOS, or FFI. Conclusion: Hallux valgus corrective surgery is a very successful procedure with high post-operative patient satisfaction. Frequently reminding a patient of the pre-operative appearance of their foot, through the use of photographs, appears to have a beneficial impact with regards to patient satisfaction in the early post-operative period.